2001
DOI: 10.1046/j.1464-410x.2001.02230.x
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomaviruses 6/11, 16/18 and 31/33/51 are not associated with squamous cell carcinoma of the urinary bladder

Abstract: Objective To assess high-risk human papillomavirus (HPV), mainly HPV type 16, 18, 31 and 33 (an important aetiological factor in squamous cell carcinoma, SCC, of the anogenital region) in SCC of the urinary bladder. Material and methods Sixteen SCC from the urinary bladder were evaluated using non-isotopic in situ hybridization with a sensitive detection system for the presence of high-risk HPV 16/18, or 31/33/51, and for HPV6/11, a low-risk type commonly found in condylomata. Previously published studies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 31 publications
2
28
1
6
Order By: Relevance
“…46 Whether HPV has a role in the carcinogenesis of bladder cancer has been debated. [47][48][49][50] Esophageal cancer (squamous cell carcinoma) has been positively associated with HPV, with a stronger association in high-risk populations, [51][52][53][54][55] but contradictory results have been reported. 56 Cigarette smoking is considered as the most important factor in the etiology of lung cancer, but detection of circulating HPV DNA in blood samples has been suggested as a risk marker for lung cancer, 57 and play a role in the carcinogenesis of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…46 Whether HPV has a role in the carcinogenesis of bladder cancer has been debated. [47][48][49][50] Esophageal cancer (squamous cell carcinoma) has been positively associated with HPV, with a stronger association in high-risk populations, [51][52][53][54][55] but contradictory results have been reported. 56 Cigarette smoking is considered as the most important factor in the etiology of lung cancer, but detection of circulating HPV DNA in blood samples has been suggested as a risk marker for lung cancer, 57 and play a role in the carcinogenesis of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Maloney et al 12 showed the presence of HPV 18 by PCR in 1 of 22 patients (4.5%) with squamous cell carcinoma while Shigehara et al 13 and Westenend et al 14 did not identify HPV in any of their 4 and 16 cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 An intriguing issue has been the possible association of the virus with bladder squamous cell carcinoma. The few published studies [11][12][13][14] on this relationship have shown a low frequency of HPV detection, implying that HPV is not likely to have a major role in the development of bladder squamous cell carcinoma. However, the positive cases identified in the literature suggest that under certain circumstances, such as immunosuppression 12 and persistent condylomatous infection, 11,15,16 the virus may exert its oncogenic activity in the bladder.…”
mentioning
confidence: 99%
“…In contrast, other studies reported no detection of HPV [7,26,33]. Several explanations of this variability have been proposed, including sampling problems, contamination, sensitivity of the detection systems, and geographic variation [34]. It seems that geographical location has an impact on the association between HPV and bladder cancer.…”
Section: Discussionmentioning
confidence: 99%